ChemInform Abstract: High‐Pressure Syntheses and Characterization of the Rare‐Earth Fluoride Borates RE2(BO3)F3 (RE: Tb, Dy, Ho). Issue 6 (11th February 2014) - Hinteregger, Ernst; Enders, Michael; Pitscheider, Almut; Wurst, Klaus; Heymann, Gunter; Huppertz, Hubert
Abstract The new title compounds are prepared under high‐pressure/high‐temperature conditions from Ln2O3 (Ln: Tb, Dy, Ho), LnF3, and B2O3 (multianvil press, BN crucible, 900—1200 °C, 1.5—3 GPa).